ERK phosphorylation mediates sildenafil-induced myocardial protection against ischemia-reperfusion injury in mice - Das, Anindita (American Physiological Society, 2009)
Sildenafil, a selective inhibitor of phosphodiesterase type 5, induces powerful protection against myocardial ischemia-reperfusion injury through activation of cGMP-dependent protein kinase (PKG). We further hypothesized that PKG-dependent activation of survival kinase ERK may play a causative role in sildenafil-induced cardioprotection via induction of endothelial nitric oxide synthase (eNOS)/inducible nitric oxide synthase (iNOS) and Bcl-2. Our results show that acute intracoronary infusion of sildenafil in Langendorff isolated mouse hearts before global ischemia-reperfusion significantly reduced myocardial infarct size (from 29.4 ± 2.4% to 15.9 ± 3.0%; P < 0.05). Cotreatment with ERK inhibitor PD98059 abrogated sildenafil-induced protection (31.8 ± 4.4%). To further evaluate the role of ERK in delayed cardioprotection, mice were treated with sildenafil (ip) 24 h before global ischemia-reperfusion. PD98059 was administered (ip) 30 min before sildenafil treatment. Infarct size was reduced from 27.6 ± 3.3% in controls to 7.1 ± 1.5% in sildenafil-treated mice (P < 0.05). The delayed protective effect of sildenafil was also abolished by PD98059 (22.5 ± 2.3%). Western blots revealed that sildenafil significantly increased phosphorylation of ERK1/2 and GSK-3β and induced iNOS, eNOS, Bcl-2, and PKG activity in the heart 24 h after treatment. PD98059 inhibited the enhanced expression of iNOS, eNOS, and Bcl-2 and the phosphorylation of GSK-3β. PD98059 had no effect on the sildenafil-induced activation of PKG. We conclude that these studies provide first direct evidence that PKG-dependent ERK phosphorylation is indispensable for the induction of eNOS/iNOS and Bcl-2 and the resulting cardioprotection by sildenafil.